Construção de um manipulador robótico com controle de posição visando o aprendizado em robótica - Pedra, André Luís Fernandes (2018)
This work describes the construction of a three-degree freedom robot as well as the implementation of a position control using voltage references arranged at each link of the manipulator. The physical model was constructed using a Cartesian 3D printer by means of deposited plastic and mounted with pitch motors for each degree of freedom. To control the movements of the robot, Fuzzy logic is used, considering only two degrees of freedom.